Physical Behavior of Partial Discharges - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
This chapter discusses the physical behavior and classification of various partial discharge (PD) types. External PD occur “outside” of any insulation equipment preferable on sharp edges or points, but also on long electrodes with small curvature or on surfaces of solid insulation. PDs that are partly or complete embedded in liquid or solid insulations are termed internal discharges. PDs on a surface may occur in any gaseous medium at their interfaces with solid dielectrics as well as at barriers in liquids. Characteristically for such so-called gliding discharges is the presence of high tangential component of electric field along the interface, which can be typically found in bushings, cable terminations, and sites in transformers, but also at outdoor and indoor insulators as principally. To evaluate PD processes in technical insulations for purposes of detection, identification and location of weak points the estimation of characteristic PD quantities is necessary.
Keywords: High voltage insulation and dielectric phenomena; Dielectric materials and actuators; Power Transformer Diagnostics and Insulation